Sistem Informasi Layanan Santunan Korpri ASN Purna Bhakti dan Meninggal Dunia Berbasis Web di Lingkungan Pemerintah Kabupaten Ogan Komering Ilir - Nita Adrianti; Andri; Firamon Syakti; Tri Oktarina (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to build a web-based KORPRI ASN compensation service information system for retired and deceased employees within the Ogan Komering Ilir District Government. This information system is a tool for presenting information in such a way that it is useful for the recipient through the services available in this system. The research material that will be used by the author includes employee data and compensation proposal data for KORPRI ASN retired and deceased in 2022. In this new system analysis, a web-based information system will be built that is used to minimize errors in recording KORPRI compensation data, so that can improve services and make reports faster and more accurate and for employees to make it easier to submit without having to come directly to the KORPRI service unit by applying the waterfall method which includes four stages, namely analysis, design, implementation and testing. This web-based information system was developed using PHP and MySQL.